Semi-green cementitious materials from waste granite by considering the environmental, economic, and health impacts: A review - Arel, H.; Shaikh, Faiz (International Federation of Prestressing, 2018)
In this review, the studies conducted on the use of recycled waste granite (WG) in place of different components in concrete or cementitious materials, such as aggregate and cement were reviewed. In this regard; research was conducted on the reuse of WG to make economic benefit, to prevent accumulation of WG, to contribute to the environment by helping in the formation of new materials from waste material, and the use of WG, which would generate hazardous radioactive gas to human health, in concrete production. Thus, the cementitious materials that will be obtained shall be environment-friendly, economic, and helpful in the isolation of hazardous radioactive wastes. Therefore, within the scope of this study, it was investigated whether semi-green cementitious materials obtained from recycling WG would have the mechanical characteristics to satisfy the requirements, and have equivalent or even surpassing characteristics compared to materials made from classic materials. The results were obtained at a substitution rate of 5–7.5%; when recycled WG was used in place of aggregate, the results were obtained at a substitution rate of 15–25%; and when recycled WG was used in place of coarse aggregate, it gave better performance than recycled normal concrete aggregate and worse performance than crushed quartzite coarse aggregate. Furthermore, in terms of economy, it was determined that the utilization of WG would decrease costs by a minimum of 0.54% and a maximum of 2.1%; while with respect to CO2 emissions, the use of WG could decrease worldwide CO2 emission by 5%. Also, it was determined that the best solution for granite, which could cause gas emissions of hazardous gases such as radon gas, would be to be used in concrete that would be exposed to open air.